MEDICAL TABLETS FROM THE ARCHIVE OF THE EGIBI FAMILY? AN EDITION OF BM 30918 AND BM 31071. (December 2021) - Simkó, Krisztián; Bácskay, András
Abstract : Building on recent advances in the field of Neo- and Late Babylonian medicine, this paper presents the edition and thorough analysis of two unpublished medical tablets from the collections of the British Museum (BM 30918 and BM 31071). In the first part, the archival and social context of these tablets will be explored, while also reporting on findings about how they might fit into the larger corpus of Late Babylonian medical texts. The two tablets are published in the second part of the paper. The aim of this paper is to illustrate that the discussed tablets contribute a lot to our understanding of how medicine as a scientific field worked in the latter half of the first millennium B.C.E. It advances further and draws up more comprehensively the thesis about the "personalisation" of medical knowledge, put forward only recently in the scholarly literature. In addition, it also collects evidence that ties Itti-Marduk-balāṭu, an important member of the Egibi family, to the craft of incantation priests ( āšipūtu ); this person has so far been known mostly for his activity as a businessman.